Habitabilidad alrededor de estrellas M: el rol de las fulguraciones - Buccino, Andrea Paola (2007)
We analyzed the UV habitable zones (UV-HZ), defined in Buccino et al. (2006), around planetary dM stars observed by IUE: HIP 74995, HIP 109388, HIP 113020 and around two dMe stars: Ad Leo and EV Lac. We found that moderate flares could be an energy source in the biogenesis processes.